2020
DOI: 10.3390/ani10071123
|View full text |Cite
|
Sign up to set email alerts
|

Behavior in Free-Living American Black Bear Dens: Parturition, Maternal Care, and Cub Behavior

Abstract: Denning behavior has long remained the least observed aspect of bear behavior. During 2010–2013, we used webcams, microphones, the internet, and 14,602 h of archived video to document the denning behaviors of two adult wild black bears (Ursus americanus) as they gave birth and cared for four litters through six winters in northeastern Minnesota. Observations included types of dens, labor, pre-parturient genital swelling, birthing positions, post-partum vocalizations, mothers removing amniotic tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As described above, we used a quantitative metabolic marker (fecal output) to align all cycles. Other bear studies have similarly used alternative non-invasively obtained, non-endocrine markers (for example temperature and activity data) to estimate implantation and birth date during hibernation [36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…As described above, we used a quantitative metabolic marker (fecal output) to align all cycles. Other bear studies have similarly used alternative non-invasively obtained, non-endocrine markers (for example temperature and activity data) to estimate implantation and birth date during hibernation [36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…To explore the motor training hypothesis, further steps in the study of spotted hyena object play are required. It would be important to trace the development of this activity covering the period from lactating to food independence and evaluate if the beginning of the independent phase coincides with the decrease of object play as suggested by Rogers et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, activity data has been used to determine parturition dates in the Scandinavian brown bear, with reduced activity levels reported during the postpartum period (Friebe et al, 2014). Furthermore, Rogers et al (2020) reported increased movements during the labor and reduced movements after delivery using cameras placed inside the den of freeranging female American black bears (Ursus americanus). Taken together, these observations provide a characteristic activity pattern that could facilitate the determination of parturition in free-ranging populations.…”
Section: Introductionmentioning
confidence: 99%